Microbiota and Endometriosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigates the relationship between microbiota composition and endometriosis in women. A sample of 60 women with endometriosis and 30 healthy women was selected for the study, focusing on differences in the abundances of key microbial species. Results showed significant changes in the microbiota of women with endometriosis, including decreased levels of beneficial bacteria such as Lactobacillus and Bifidobacterium, and increased levels of pathogenic bacteria such as Escherichia coli. These findings suggest that dysbiosis may play a role in the pathogenesis of endometriosis, which holds promise for the development of therapeutic strategies aimed at restoring the normal microbiome.